Platelet-to-Portal Vein Width Ratio and Platelet-to-Spleen Thickness Ratio Can Be Used to Predict Progressive Liver Fibrosis Among Patients With HBV Infection With HBeAg-Negativity and a Normal ALT Level - Feng, Mudan; Lei, Lan; Xu, Jian; Shi, Yuzhi; Yang, Wenfeng (Frontiers in Medicine, 2022)
Background: Some people infected with the hepatitis B virus (HBV) with a normal level of alanine aminotransferase (ALT) are at risk of disease progression. We evaluated the value of platelet-to-portal vein width ratio (PPR) and platelet-to-spleen thickness ratio (PSR) to predict advanced liver fibrosis among patients with HBV infection with HBV e antigen (HBeAg)-negativity and a normal ALT level. Methods: HBV surface antigen (HBsAg)-positive and HBeAg-negative individuals with a normal ALT level were enrolled. The inflammation grade (G) and fibrosis stage(S) were analyzed according to pathological features. Then, two groups (0.05).The platelet count, PPR, and PSR were significantly different between the two groups ((145.92±14.55) ×109/L vs. (126.38±23.85) ×109/L, p =0.008; 10.80±1.30 vs. 9.01±1.97, p =0.004; 4.21±0.65 vs. 3.33±0.89, p =0.02, respectively). The PPR and PSR decreased gradually upon fibrosis aggravation (p<0.05). Based on the cut off value of the PPR (9.07) and PSR (3.54), their sensitivity and specificity was 0.917and 0.525, and 0.833 and 0.541, respectively. Conclusion: The PPR and PSR can be employed to assess fibrosis progression among patients with HBV infection with HBeAg-negativity and a normal ALT level.